Comparative study of DOTS treatment outcomes among pulmonary tuberculosis patients at Bondongan and Bogor Timur primary health centers - Sondang Khairani; Reise Manninda; Lusiana Ariani; Sabina Radya Harumi (JURNAL ILMU KEFARMASIAN INDONESIA, 2026)
Tuberculosis (TB) remains a major infectious disease and a significant public health concern in Indonesia. The Directly Observed Treatment Short-course (DOTS) strategy has been widely implemented to improve treatment adherence and outcomes among patients with TB. This study aimed to compare the treatment outcomes of patients with pulmonary tuberculosis undergoing DOTS therapy at Bondongan Primary Health Center and Bogor Timur Primary Health Center. This study used a descriptive and inferential research design with retrospective data collection conducted in 2024. A total of 159 patients with pulmonary TB were included in the study. Data were analyzed based on patient characteristics, including age, sex, comorbidities, type of diagnosis, duration of treatment, and treatment outcomes. The results showed that the majority of patients at Bondongan Primary Health Center were aged 38–47 years (30.13%), whereas most patients at Bogor Timur Primary Health Center were aged 18–27 years (36.03%). Female patients accounted for 54.10% of the total population. Most patients received six months of treatment (84.91%), were bacteriologically confirmed (76.10%), and all patients received fixed-dose combination (FDC) therapy. At Bondongan Primary Health Center, the comorbidity status of diabetes mellitus (DM) was largely unknown (80.82%), whereas most patients at Bogor Timur Primary Health Center had no DM comorbidity (87.21%). The treatment success rates were 83.56% and 97.67% at the Bondongan and Bogor Timur Primary Health Centers, respectively. Statistical analysis indicated that patient characteristics were not significantly associated with treatment success (p≥0.05).